2014
DOI: 10.1371/journal.pone.0089077
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Exclusive Breastfeeding of Preterm Infants. Results from a Prospective National Cohort Study

Abstract: Background and AimEvidence-based knowledge of how to guide the mothers of preterm infants in breastfeeding establishment is contradictive or sparse. The aim was to investigate the associations between pre-specified clinical practices for facilitating breastfeeding, and exclusive breastfeeding at discharge as well as adequate duration thereof.MethodsA prospective survey based on questionnaires was conducted with a Danish national cohort, comprised of 1,221 mothers and their 1,488 preterm infants with a gestatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
168
3
19

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(203 citation statements)
references
References 46 publications
13
168
3
19
Order By: Relevance
“…Incorrect feeding practices like feeding formula milk or anything other than breast milk and bottle feeding were shown to be significantly associated which must have been due to the poor knowledge on the importance of exclusive BF and the adverse outcomes of formula or other feeds which also showed significant association with difficulties in BF in this study. Two community based study showed similar results 14,17 .…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Incorrect feeding practices like feeding formula milk or anything other than breast milk and bottle feeding were shown to be significantly associated which must have been due to the poor knowledge on the importance of exclusive BF and the adverse outcomes of formula or other feeds which also showed significant association with difficulties in BF in this study. Two community based study showed similar results 14,17 .…”
Section: Discussionsupporting
confidence: 55%
“…Neonatal birth weight less than 2500g or more than 3500g and the period of amenorrhoea less than 37 weeks were also not associated with BF status which could also be due to the fact that some of the extreme premature and extreme low birth weight babies are admitted to the SCBU. A Danish study also revealed that 68% of premature babies exclusively breast fed on discharge 17 .…”
Section: Discussionmentioning
confidence: 99%
“…This article is the second from the cohort; the first article analysed factors associated with exclusive breastfeeding at discharge and adequate duration [14].…”
Section: Methodsmentioning
confidence: 99%
“…Certainly the speeches describing sadness, frustration and guilt reflect negative feelings of failure in breastfeeding, which are part of the repertoire of so many other testimonies of women who desire and try hard to maintain breastfeeding, regardless of the biological conditions associated with surgery (16)(17) . However, among women who undergo breast surgeries, these emotions collide with the desire and persistence for maintaining breastfeeding with relactation and formula.…”
Section: Discussionmentioning
confidence: 99%